Patriachal oppression of bedouin Egyptian women in selected novels by Miral al Tahawl: an analytical study in light of radical feminist theory - Hammood, Zainab Abd Ali (2020)
The study aims to analyze the patriarchal system, the patriarchal oppression towards female characters, and women's resistance to this patriarchal oppression in selected novels by Miral Al Tahawi namely The Tent, Blue Aubergine, Gazelle Tracks, and Brooklyn Heights. Radical feminism theory is used to analyze the selected texts as it considers patriarchy as the main root of women's oppression. The objectives of the research shed light on the oppressive patriarchal authority that uses its power to oppress Bedouin women, the types of oppression that Bedouin women are subjected to by the norms of oppressive patriarchal system, and the way Bedouin women resist patriarchal oppression. The study finds that, despite the strict Bedouin patriarchal system which imposes its oppressive rules on women, the Bedouin women try to release these restrictions in several ways. AI-Tahawi manages to provide a sense of identity for the female characters to free them from the oppression through education, self-awareness, and solidarity between women in resisting the patriarchal society, even if the resistance may lead to their death. As a conclusion, Bedouin women are a victim of strict patriarchal Bedouin customs that consigns them as the "other" in the society in the way that their lives are managed and controlled by the men. In order to free themselves, women must educate and unite and recognize that they are oppressed. The implications of the study indicated the power of the patriarchal system in the Bedouin community in shaping and controlling the lives of its women until the twenty-first century, and that it is necessary to shed light on the suffering of women politically, socially and economically in order to advance their reality for the better.